PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP INTERAKSI SOSIAL PADA MAHASISWA PRODI MANAJEMEN INFORMASI KESEHATAN - Simbolon, Pomarida; Marbun, Kajol Santa Monika (LPPM UM Metro, 2025)
In everyday life, the process of individual relationships with other individuals or society is carried out through social interaction. An individual's social development is greatly influenced by the social interaction skills he or she performs. Intensity is related to frequency, namely how often the activity is carried out. Gadget users now spend more time with their gadgets than chatting or just spending time together with other family members. Uncontrolled use of gadgets like this can interfere with the process of social interaction. The relationship or influence of the intensity of gadget use on social interaction is very strong. The higher the intensity of gadget use, the lower the pattern of social interaction. And vice versa, if the Intensity of Gadget Use is lower, the higher the Social Interaction. The purpose of this study was to identify the effect of the Intensity of Gadget Use on social interaction in Health Information Management Study Program Students. The analytical research design used a cross-sectional approach. The sample of this study was 62 respondents with a sampling technique of total sampling, namely the entire population was used as a research sample. The instrument used was a questionnaire. Data analysis using the Chi-square test. The results of this study obtained a high intensity of gadget use in 7 students (58.3%) and a low intensity of 5 students (10.0%). high social interaction in students as many as 5 people (41.7%) and low as many as 45 people (90.0%). The results of the chi-square statistical test on the effect of the intensity of gadget use on social interaction in students of the Health Information Management Study Program. showed that from 62 respondents obtained a pvalue = 0.001 (p value <0.05). There is an effect of the intensity of gadget use on social interaction in students of the Health Information Management Study Program. It is expected that students of the Health Information Management Study Program will reduce the intensity of gadget use, and use gadgets as needed, Use time to study and communicate with others to increase social interaction every day.